The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.3390/nu5030852
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Amino Acids, Dietary Protein, and Physical Activity on Muscle Mass Development in Humans

Abstract: Ingestion of protein is crucial for maintenance of a variety of body functions and within the scope of this review we will specifically focus on the regulation of skeletal muscle mass. A quantitative limitation exists as to how much muscle protein the body can synthesize in response to protein intake. Ingestion of excess protein exerts an unwanted load to the body and therefore, it is important to find the least amount of protein that provides the maximal hypertrophic stimulus. Hence, research has focused on r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
69
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(69 citation statements)
references
References 156 publications
(270 reference statements)
0
69
0
Order By: Relevance
“…Previous studies clearly suggested that fast-digested and slow-digested proteins have synergistic effects on muscle anabolism (Dideriksen et al, 2013;Boirie et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies clearly suggested that fast-digested and slow-digested proteins have synergistic effects on muscle anabolism (Dideriksen et al, 2013;Boirie et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…[69][70][71][72] Because protein ingestion is crucial for the maintenance of a variety of body functions, the requirements of protein in the elderly are a major factor in maintaining skeletal muscle mass; the amount of protein ingested that induces maximal muscle protein synthesis must be higher in elderly than in young individuals in order to combat anabolic resistance in the elderly. 5,[73][74][75][76][77] Dysregulation of autophagy [78][79][80] contributes notably to aging. Autophagy, a lysosomal process involved in the maintenance of cellular homeostasis, is inhibited by the insulin-amino acid-mTOR signaling pathway that controls both protein synthesis and longevity (see next paragraph).…”
Section: Impact Of Aging On Regulation Of Glutamine Metabolismmentioning
confidence: 99%
“…However, while the decrease in the male participants was statistically significant, the decrease in the female participants was not statistically significant. A plausible reason for this decrease in total protein value has been suggested [21][22][23], to be due to increased demand of glucogenic amino acids for the generation of energy leading to increased degradation of proteins. A similar result was obtained for plasma albumin.…”
Section: Discussionmentioning
confidence: 99%